How does the efficacy and safety of Oralair® compare to other products on the market? - Larenas-Linnemann D (Dove Medical Press, 2016)
Désirée Larenas-Linnemann Pediatric Allergy and Asthma Clinic, Department of Investigation, Hospital Médica Sur, México City, México Abstract: Due to differences between allergen immunotherapy (AIT) trials in patient populations, trial design (including primary efficacy variables), the definition of a pollen season, data analysis, and comparisons between AIT products with existing data, is not possible nor valid. The efficacy of two grass pollen AIT tablets, Oralair® and Grazax®/Grastek®, should not be compared by looking at the percentage of score improvement in their respective trials. However, the evidence available concerning the efficacy and safety in trials can be compared by paying close attention to the scientific quality of the trials, details in the administration schedules, and safety issues. It can be concluded due to the high level of evidence available, that Oralair® is effective in a pre (2-months)-coseasonal schedule to reduce symptoms and medication use, and improve a patients’ quality of life during the treatment season. For the long-term, where the quality of efficacy evidence is moderate at 2-year posttreatment due to a high dropout rate, the pre (4-months)-coseasonal schedule should be used. No clinical efficacy data exists for starting treatment in-season, but the clinical onset of action of Oralair® is detectable after only 1 month of treatment. In the pivotal trials in Europe and the USA, no tablet-related epinephrine was needed, though some rare severe local reactions have been reported. Research for Grazax®/Grastek® showed that the long-term efficacy needs a continuous 3-year administration (moderate-low quality evidence available), and in two patients, tablet-related epinephrine was given. Further details on the comparative efficacy of both tablets would only be possible if both were evaluated in the same, adequately powered trial. Keywords: sublingual allergen immunotherapy, grass pollen, allergic rhinitis, allergic conjunctivitis, tablet allergen immunotherapy